Pseudoalveolar Form of Sarcoidosis: Etiology of Biological, Histological and Radiological Findings - Chaynez Rachid; Saad Bounhar; Lamyae Amro (Current Overview on Disease and Health Research Vol. 11, 2023)
Sarcoidosis is a benign systemic granulomatosis with an unknown cause. Parenchymal involvement in the interstices is typical. The pseudoalveolar type is uncommon, frequently acute in onset, and challenging to identify, but it quickly gets better with corticosteroid treatment. Here, we present a case of pseudoalveolar sarcoidosis in a young female patient with a distinctive and perplexing radiological and clinical presentation. In this work, we highlight the rarity of this pseudoalveolar type, the challenge of an early identification, and the significance of taking it into consideration. However, in 25% to 30% of cases, the radiological findings are atypical and unfamiliar to most radiologists, making a correct diagnosis difficult. There have been numerous reports of atypical forms of intrathoracic sarcoidosis. We gathered a case of unusual radiological finding and described a disorder typical form. Finally, we discuss the excellent response of this unusual form of sarcoidosis to corticosteroid therapy and the importance of starting therapy early.